2008
DOI: 10.1116/1.3021361
|View full text |Cite
|
Sign up to set email alerts
|

Plasma atomic layer etching using conventional plasma equipment

Abstract: The decrease in feature sizes in microelectronics fabrication will soon require plasma etching processes having atomic layer resolution. The basis of plasma atomic layer etching ͑PALE͒ is forming a layer of passivation that allows the underlying substrate material to be etched with lower activation energy than in the absence of the passivation. The subsequent removal of the passivation with carefully tailored activation energy then removes a single layer of the underlying material. If these goals are met, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
106
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(111 citation statements)
references
References 39 publications
1
106
0
4
Order By: Relevance
“…By working close to the energy threshold for physical sputtering of one material, and exploiting energy threshold differences among different materials, etching selectivity can be optimized. 9 The threshold energy for physical sputtering E psth depends on the nature of the material and is higher in the case of SiO 2 than for Si, E psth (SiO 2 )>E psth (Si). By supplying chemical reactant to the substrate surface, chemically enhanced etching is possible, with an energy threshold E ceth (SiO 2 ) that is lower than for physical sputtering E psth (Si), which may enable selective etching of SiO 2 over Si.…”
Section: Ecs Journal Of Solid State Science and Technology 4 (6) N50mentioning
confidence: 99%
See 4 more Smart Citations
“…By working close to the energy threshold for physical sputtering of one material, and exploiting energy threshold differences among different materials, etching selectivity can be optimized. 9 The threshold energy for physical sputtering E psth depends on the nature of the material and is higher in the case of SiO 2 than for Si, E psth (SiO 2 )>E psth (Si). By supplying chemical reactant to the substrate surface, chemically enhanced etching is possible, with an energy threshold E ceth (SiO 2 ) that is lower than for physical sputtering E psth (Si), which may enable selective etching of SiO 2 over Si.…”
Section: Ecs Journal Of Solid State Science and Technology 4 (6) N50mentioning
confidence: 99%
“…While average ion energy has been shown to be useful, 9 careful studies of the impact of ion energy distributions on ALE performance are required to answer the question how closely ion energies must be controlled to enable optimal exploitation of the ALE window. Shin et al 46 investigated nearly mono-energetic ion energy distributions (IEDs) and observed novel phenomena (see below).…”
Section: Atomic Layer Etching (Ale)mentioning
confidence: 99%
See 3 more Smart Citations